2016
DOI: 10.1155/2016/3951703
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silicon-Containing Chitosan Hydrogels in a Glycolic Acid Medium

Abstract: The present paper considers a “one-pot” green sol-gel synthesis of hybrid inorganic/organic hydrogels based on chitosan glycolate by using organically modified silica Si(OGly)4·2GlyOH as a precursor to form a network of ≡Si–O–Si≡ bonds at 4, 20, and 37°C. The gelation time of the multicomponent chitosan-containing system was estimated as a function of the composition (the polymer template and precursor concentrations, introduction of a low-molecular-weight accelerator NaCl) and gelation conditions (the pH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…The revealed differences in the chirality of l - and d -diastereomerically-enriched chitosan ascorbates exert a significant influence on the kinetics of the biomimetic sol–gel synthesis of silicon-chitosan-containing glycerohydrogels. Previously, it was shown that the gelation kinetics of the systems based on chitosan salts and silicon tetraglycerolate was controlled by the acidity of the medium, determined by the nature and acid-base properties of the acid used [ 19 , 26 , 27 ]. Taking into account the same pH values of the source gelling systems, we associate the retarding or accelerating effect of chitosan ascorbate with the stereoisomerism of the chiral ligand and, correspondingly, with features of the spatial structure of the corresponding polysalt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The revealed differences in the chirality of l - and d -diastereomerically-enriched chitosan ascorbates exert a significant influence on the kinetics of the biomimetic sol–gel synthesis of silicon-chitosan-containing glycerohydrogels. Previously, it was shown that the gelation kinetics of the systems based on chitosan salts and silicon tetraglycerolate was controlled by the acidity of the medium, determined by the nature and acid-base properties of the acid used [ 19 , 26 , 27 ]. Taking into account the same pH values of the source gelling systems, we associate the retarding or accelerating effect of chitosan ascorbate with the stereoisomerism of the chiral ligand and, correspondingly, with features of the spatial structure of the corresponding polysalt.…”
Section: Discussionmentioning
confidence: 99%
“…We considered the biomimetic sol-gel synthesis of silicon-chitosan-containing glycerohydrogels using glycerol solutions of silicon tetraglycerolate and aqueous solutions of chitosan salts with organic (СН 3 СООН, HOOCCH 2 OH, and С 6 Н 8 О 6 ) and inorganic (HCl) acids [ 19 , 26 , 27 ]. The influence of the concentration of the precursor and chitosan salt, the pH of the medium and the temperature of the sol–gel process on the gelation time of the multicomponent chitosan-containing system was estimated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ранее нами рассмотрен биомиметический золь-гель синтез кремнийхитозансодержащих глицерогидрогелей с использованием глицериновых растворов тетраглицеролата кремния и умеренно концентрированных водных растворов солей хитозана с органическими и неорганическими кислотами: уксусной, гликолевой, аскорбиновой, соляной [20,26,27]. Оценено влияние концентрации предшественника и соли хитозана, рН среды и температуры проведения золь-гель процесса на время гелеобразования многокомпонентной хитозансодержащей системы.…”
Section: Doi: 1018500/1816-9775-2018-18-2-154-162unclassified